The effectiveness of co-curricular activities by integrated living skills unit in enhancing students’ soft skills - Nur Munirah Roslan; Mohamad Shukri Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Co-curriculum is a vital part of an education system that helps students to build their soft skills. Co-curricular activity is activities that usually complement regular co-curriculum. In order to produce holistic students, students need to have excellent interpersonal skills that can be developed through co-curricular activities in their college. Therefore, this paper aims to determine the effectiveness of Co-Curricular activities in enhancing students’ soft skills. This study was conducted on students who enrolled in the third and fourth semester of Co-curricular in Integrated Living Skills unit at University Utara Malaysia and the data were obtained through the dissemination of survey questionnaire with randomly selected students. The primary data involve a large population of students about 510 students and the co-curricular unit have been group into four groups that are Scout, Outrec, Kor Siskor and Basic of Car Maintenance. The data were analyzed using Gap Analysis, Paired Independence T-test, t-test and Chi-Square. The data were collected using Stratified Random Sampling where the strata are the four stated co-curricular activities and the respondent are randomly selected. A gap analysis was used to examine the different level of students’ soft skill before and after co-curricular activities that compulsory to all the students before graduation. Generally, the result shows that the students’ level of soft skills is improving after they attend the co-curricular activities and the widest gap was in interpersonal skills, especially the skills of the ability to work and contribute to the group. However, critical research should be done in order to identify the overall co-curriculum unit on the effectiveness of students’ soft skills.